Natural enemies of the maize cob borer Mussidia nigrivenella (Lepidoptera: Pyralidae) in Benin, West Africa - Sétamou, M.; Schulthess, F.; Goergen, Georg E.; Poehling, H.M.; Borgemeister, C. (Cambridge University Press, 2002)
Mussidia nigrivenella Ragonot is a pest of maize cobs in West Africa. It significantly reduces maize yields and grain quality, with quantitative losses of 2–25% at harvest, and up to 10–15% indirect losses due to an increase in storage pest infestation levels. Infestation by M. nigrivenella also significantly increased the susceptibility of maize to Aspergillus flavus infection and subsequent aflatoxin contamination. Surveys conducted in different agro-ecological zones of Benin on cultivated and wild host plants during 1994–1997 revealed one egg parasitoid, three larval parasitoids and one pupal parasitoid attacking M. nigrivenella. Egg parasitism was scarce on all host plants sampled and in all four agro-ecological zones. Parasitism by larval and pupal parasitoids was usually less than 10%, and varied with host plant species. Both larval and pupal parasitoids were rare or absent in cultivated maize fields. The solitary chalcidid pupal parasitoid, Antrocephalus crassipes Masi, was the predominant species, contributing approximately 53% of the observed mortality. Logistic regression analysis indicated that this parasitoid was more prevalent on fruits of Gardenia spp. (Rubiaceae) than on the other host plant species including maize used by M. nigrivenella, and was most abundant between February and September. The differences in parasitoid diversity and parasitism between Benin and other regions suggest that there are opportunities for biological control through introduction of exotic parasitoids or using the ‘new association' approach, which uses natural enemies of closely related host species that occupy similar ecological niches to the target pest.